Relationship Between Summer Compound Hot and dry Extremes in China and the Snow Cover Pattern in the Preceding Winter - Yao, Haoxin; Zhao, Liang; Shen, Xinyong; Xiao, Ziniu; Li, Qingquan (Frontiers in Earth Science, 2022)
With global warming, the probability of summer compound hot and dry extreme (CHDE) days, which are higher risk compared with single-factor extreme events, increases in some regions. However, there have been few studies on the winter precursor signals of such events. In this study, we found that summer CHDEs have generally increased in the last 20 years, with the increases in the middle and lower reaches of the Yangtze River region and Southwest China being more than double those in other regions of China. The dominant mode of summer CHDEs in China is characterized by more hot–dry days in the Yangtze–Huaihe River Basin (YHRB). Importantly, we found that there is an obvious cross-seasonal relationship between the first mode of winter snow cover in the Northern Hemisphere (NH) and summer CHDEs in China. When the mode of winter snow cover in the NH is in a positive phase with a negative-phase Arctic Oscillation (AO), i.e., more snow cover in Europe, Northeast China, and the northern United States, and less snow cover in central Asia and the midlatitudes in winter, more CHDEs in China in the following summer. Compared with the signals from the AO, these signals from winter snow can be better stored and transmitted into summer through the snow, soil and ocean, inducing a northward shift of the upper-level westerly jet and strengthening of South Asia high. Through the strong dynamic forcing of negative vorticity advection with the change of westerly jet, the subsidence movement in the western Pacific subtropical high (WPSH) region is strengthened, resulting in the stable maintenance of the WPSH in the YHRB. Under the synergy of a remote mid- and high-latitude wave train in summer, which also relates closely to winter snow cover, more CHDEs ultimately occur in the YHRB of China.